2022
DOI: 10.1177/00469580221129168
|View full text |Cite
|
Sign up to set email alerts
|

Concern for Patient Safety Culture of ECMO Team in Emergency Department: A Cross-Sectional Survey

Abstract: To evaluate the patient safety culture status of the ECMO team in the emergency department of a tertiary care hospital. A cross-sectional survey was conducted in the emergency department of Xiangya Hospital from September 1st to 30th, 2021. The Chinese version of HSOPSC electronic questionnaire was administered to all staff involved in ECMO management and initiation. A total of 152 ECMO team members completed the survey. Among the 12 dimensions of patient safety culture, 4 dimensions recorded relatively high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The SOP of patient safety culture is to measure the perceptions of nurses in connection with patient safety work standards in their respective work units, the perceptions of managers/supervisors/ heads of units on how to promote patient safety work standards, communications from nurses related to patient safety and medical errors, and reporting of patient safety incidents in work units by the nurse. (16) The measurements demonstrated validity, usability, feasibility, internal consistency, and reliability (Cronbach alpha = 0.94). (17) Patient safety culture in each dimension has several questions with positive and negative statement aspects.…”
Section: Measurementsmentioning
confidence: 92%
See 1 more Smart Citation
“…The SOP of patient safety culture is to measure the perceptions of nurses in connection with patient safety work standards in their respective work units, the perceptions of managers/supervisors/ heads of units on how to promote patient safety work standards, communications from nurses related to patient safety and medical errors, and reporting of patient safety incidents in work units by the nurse. (16) The measurements demonstrated validity, usability, feasibility, internal consistency, and reliability (Cronbach alpha = 0.94). (17) Patient safety culture in each dimension has several questions with positive and negative statement aspects.…”
Section: Measurementsmentioning
confidence: 92%
“…There were 20 nurses were excluded based on the exclusion criteria. The research sample of 80 nurses was divided equally among 5 hospitals based on hospital clusters (16 nurses in each hospital). A random sample to reduce bias and to estimate the prevalence of unknown parameter(s) from the target population.…”
Section: Study Subjectsmentioning
confidence: 99%
“…[4][5][6][7] According to the Extracorporeal Life Support Organization (ELSO) statistic, 8,9 as of April 18, 2023, a total of 16,803 cases of ECMO were conducted in the year 2022, with a cumulative total of 196,108 cases, and 54% of the patients survived to hospital discharge or transfer. However, ECMO is technically complex, demanding, and challenging to manage during operation; 10,11 Therefore, it often requires specialized teamwork, and ECMO nurses play a significant role during the treatment or management of ECMO patients. 12 Previous studies have shown that 55% of patients experienced complications such as hemorrhage and cerebral infarction during ECMO support due to inadequate monitoring of their condition, and the cumulative incidence of 90-day in-hospital mortality was 37.4%.…”
Section: Introductionmentioning
confidence: 99%